تأثير البروتوكولات الاستباقية والتفاعلية والهجينة على أداء الشبكات اللاسلكية MANET - حجازية, محمد; يونس, معين; عباس, بشار (Latakia University Journal -Engineering Sciences Series, 2017)
شبكاتAd-hoc فتحت بعدا جديدا في الشبكات اللاسلكية. فإنها تسمح للعقد اللاسلكية التواصل في غياب الدعم المركزي . في هذه الشبكات لا توجد بنية تحتية ثابتة لان العقد متحركة بشكل مستمر مما يسبب تغير مستمر وديناميكي في الطبولوحيا. تختلف برتوكولات التوجيه في شبكات Ad-hoc عن برتوكولات الانترنت العادية المصممة من أجل الشبكات اللاسلكية ببنية تحتية ثابتة , برتوكولات التوجيه في شبكات MANETتواجه تحديات كبيرة بسبب التغير الدائم في الطبولوجيا ,الارتباط الغير متماثل ,انخفاض الطاقة اللازمة للانتقال، الطبولوجيا المتغيرة , وحركية العقد المستمرة وتعتبر هذه التحديات من القضايا المهمة التي تميز شبكات MANET .توفر بروتوكولات التوجيه حلول توجيه جيدة تصل إلى مستوى مقبول ومعظمها تم تصميمها وتنفيذها لتوجد الحلول المناسبة لمشاكل الشبكات اللاسلكية من حيث الطبولوجيا المتنقلة و الحركية في العقد . ومع زيادة أنواع بروتوكولات التوجيه المستخدمة في الشبكات المحمولة أصبح من الضروري دراسة فاعلية كل نوع من البروتوكولات وفي هذا البحث تمت المقارنة بين الأنواع الأكثر شهرة للبرتوكولات( الاستباقية , التفاعلية , الهجينة ) تم تقييم أداء الشبكة لكل نوع البروتوكولات كلا على حده من حيث المردود Throughput, حركية التوجيه Routing Traffic Sent, الحمل Load, التأخير Delay وتحديد أي من هذه البروتوكولات مناسب لكل حالة . Ad-hoc networks has opened a new dimension in wireless networks. It allows wireless communication in the absence of central support of the contract. In these networks, there are no fixed infrastructure because the mobile nodes are continuously making continuous and dynamic change in the topology. Routing protocols of mobile ad-hoc networks differ from the existing internet protocols which are designed for the fixed structure based wireless networks. MANET protocols have to face high challenges due to dynamically changing of topologies, low transmission power and asymmetric links. Due to link instability, node mobility and frequently changing topologies routing becomes one of the core issues in MANETs.Currently existent routing protocols provide routing solutions up to a certain level and most of them are designed and implemented in small areas. Many researchers are still working on the developments of MANET routing protocols.With the increase in the types of routing protocols used in mobile network it has become necessary to study the effectiveness of each type of protocols In this papper we compared between the most famous species (proactive, Reactive, hybrid) and choose a protocol to be representative of all species previously mentioned and the network performance assessment each type in terms of Throughput, dynamic routing routing, load, delay and determine which of these protocols appropriate for each case.